TECTONIC SETTING OF MESOZOIC MAGMATISM: A COMPARISON BETWEEN NORTHEASTERN RUSSIA AND THE NORTH AMERICAN CORDILLERA - Miller E.L.; Hourigan J.; Gelman M.; Parfenov L. (My University, 2002)
Early to Middle Triassic rift-related basaltic magmatism occurred along the entire length of the northern circum-Pacific margin and was followed by Triassic to Early Jurassic (230-190 Ma) development of marine island arcs and deep-water basins. The inception of deformation in the Middle Jurassic brought an end to this tectonic regime. In northeastern Russia and Alaska, deformation was over by Middle Jurassic (Bathonian), but shortening continued in an Andean setting until ca. 160-150 Ma in the United States and Canada. Marine basins closed, marginal arc systems were accreted, and calc-alkaline batholiths developed in concert with backarc deformation, while in Alaska and Russia, mostly subsidence occurred. The Siberian margin subsequently experienced deformation, terrane accretion, magmatism, and batholith emplacement between ca. 150-125 Ma, while a conspicuous lull in magmatism and tectonism occurred in the Canadian and U.S. Cordillera. During ca. 125-170 Ma, the Okhotsk volcanic belt developed in northeastern Russia during minor extension. Magmatism began again in the Cordillera ca. 130-120 Ma, but instead was accompanied by significant crustal shortening and plutonism, continuing into the Tertiary. This comparison indicates that striking similarities exist for event boundaries for magmatism and deformation, but fundamental differences are evident in the tectonic setting for magmatism through time, suggesting that plate motions, coupled at least at the scale of the northern Pacific, are responsible for the recorded events and their duration(s). Along-strike changes appear to take place in Alaska, which has a Mesozoic history similar to Russia, and was also affected by Arctic plate motions.
Keywords: Mesozoic; Mesozoic; Мезозой